2023
DOI: 10.2147/dddt.s427837
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Effect of Compound Anoectochilus roxburghii (Wall.) Lindl. Oral Liquid in Treating Alcoholic Rat Liver Injury by Metabolomics

Tingxuan Huang,
Youjia Wu,
Lingyi Huang
et al.

Abstract: Compound Anoectochilus roxburghii (Wall.) Lindl oral liquid (CAROL) is often as a hepatoprotective agent. The present study aimed to elucidate the protective mechanism of CAROL against alcoholic liver injury in rats by untargeted metabolomics combined with multivariate statistical analysis. Methods: An alcoholic liver disease model was established in sprague-dawley (SD) rats by gavage of alcohol, and CAROL treatment was administered. The hepatoprotective effect of CAROL was evaluated by examining liver tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…Of note, arginine and proline metabolism are importantly implicated in pregnancy and in protecting the host from damage [71]. They possess ROS scavenging properties, helping to maintain stable glutathione levels [72], and proline is inhibitory for liver inflammation [73]. In addition, we have observed that the changes in host metabolic products induced by MA are significantly correlated with alterations in gut microbiota as well as anti-inflammatory and antioxidant responses.…”
Section: Discussionmentioning
confidence: 79%
“…Of note, arginine and proline metabolism are importantly implicated in pregnancy and in protecting the host from damage [71]. They possess ROS scavenging properties, helping to maintain stable glutathione levels [72], and proline is inhibitory for liver inflammation [73]. In addition, we have observed that the changes in host metabolic products induced by MA are significantly correlated with alterations in gut microbiota as well as anti-inflammatory and antioxidant responses.…”
Section: Discussionmentioning
confidence: 79%